MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS MAHASISWA UIN SU MEDAN PADA MATAKULIAH STATISTIKA MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN ARIAS - Eka Khairani Hasibuan (State Islamic University of North Sumatra, 2018)
The aims of this research are intended to examine the effect ofARIAS learning model toward the increase of student'smathematical understanding ability. The research utilizednonequivalent pre-test and post control group design. Thepopulation of this research are students ofFITK UINSU Medan. Asconcern, the sample comprised of 32 students in ARIAS class(experiment group) and 33 students in conventional class (controlgroup). The research problem are to improve mathematicalunderstanding ability. The quantitative analysis is usedindependent sample t-test, Mann-Whitney test, while qualitativeanalysis is used descriptive one. The result shows better increasingmathematical understanding ability by using ARIAS learningmodel than by using conventional teaching.